2017
DOI: 10.3390/ncrna3040025
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Non-Coding RNA in Sugarcane-Microbe Interaction

Abstract: Studies have highlighted the importance of non-coding RNA regulation in plant-microbe interaction. However, the roles of sugarcane microRNAs (miRNAs) in the regulation of disease responses have not been investigated. Firstly, we screened the sRNA transcriptome of sugarcane infected with Acidovorax avenae. Conserved and novel miRNAs were identified. Additionally, small interfering RNAs (siRNAs) were aligned to differentially expressed sequences from the sugarcane transcriptome. Interestingly, many siRNAs aligne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…The IbKCS cleavage sites guided by miR408 are located at the 5th and 10th nucleotides from the 5′ end, which are non-canonical and canonical cutting sites, respectively [ 44 ]. In S. officinarum , the Diphenol oxidase laccase cleavage sites guided by miR408 are located at the second to third nucleotides from the 5′ end [ 64 ]. In M. truncatula , m iR408 cleaved PLC at the 10th–11th nucleotides from the 5′ end [ 41 ].…”
Section: Overview Of the Mir408 -Regulated Target Genesmentioning
confidence: 99%
“…The IbKCS cleavage sites guided by miR408 are located at the 5th and 10th nucleotides from the 5′ end, which are non-canonical and canonical cutting sites, respectively [ 44 ]. In S. officinarum , the Diphenol oxidase laccase cleavage sites guided by miR408 are located at the second to third nucleotides from the 5′ end [ 64 ]. In M. truncatula , m iR408 cleaved PLC at the 10th–11th nucleotides from the 5′ end [ 41 ].…”
Section: Overview Of the Mir408 -Regulated Target Genesmentioning
confidence: 99%
“…In addition to genetic mechanisms, diazotrophic bacteria can trigger specific epigenetic modifications that regulate development [ 171 ] and cell wall lignification [ 101 , 172 ]. Epigenetic studies on sugarcane plants have revealed the differential expression of miR408 in response to either diazotrophic bacteria, G. diazotrophicus PAL5, or the pathogenic bacteria Acidovorax avenae [ 172 ].…”
Section: Molecular Mechanisms Involved In the Association Of Plant An...mentioning
confidence: 99%
“…In addition to genetic mechanisms, diazotrophic bacteria can trigger specific epigenetic modifications that regulate development [ 171 ] and cell wall lignification [ 101 , 172 ]. Epigenetic studies on sugarcane plants have revealed the differential expression of miR408 in response to either diazotrophic bacteria, G. diazotrophicus PAL5, or the pathogenic bacteria Acidovorax avenae [ 172 ]. MiR408 was induced in response to beneficial association and repressed upon pathogenic infection, regulating the expression of mRNA encoding laccase, a multicopper enzyme involved in lignin biosynthesis [ 172 ].…”
Section: Molecular Mechanisms Involved In the Association Of Plant An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications reported the identification of miRNAs in biofuel crops such as Miscanthus giganteus(Jha & Shankar, 2013), Setaria italica(Yadav, Muthamilarasan, Pandey, Khan, & Prasad, 2014;Yi, Xie, Liu, Qi, & Yu, 2013), Sorghum bicolor(Calviño, Bruggmann, & Messing, 2011), Z. mays(Aravind et al, 2017;Liu et al, 2019), and Saccharum sp. (Gentile, Dias, Mattos, Ferreira, & Menossi, 2015 and references therein;Li et al, 2017;Thiebaut et al, 2017;Su et al, 2017;Yang et al, 2017). However, only a few of them addressed specific miR-NAs predicted to be involved in cell wall construction or remodeling.In the present work, we identified 39 miRNAs expressed within the roots of the biofuel crop sugarcane undergoing cell wall changes due to aerenchyma formation.…”
mentioning
confidence: 99%